Complications of Arthroscopic Versus Open Biceps Tenodesis in the Setting of Arthroscopic Rotator Cuff Repairs: An Analysis of the American Board of Orthopaedic Surgery Database. Issue 3 (1st February 2020) - Yeung, Marco; Shin, Jason J.; Lesniak, Bryson P.; Lin, Albert
Abstract : Introduction: The purpose of this study was to compare complication rates between arthroscopic versus open biceps tenodesis in the setting of arthroscopic rotator cuff repair and to determine the effect of fellowship training on complication rates. Methods: The American Board of Orthopaedic Surgery database was used to identify cases of arthroscopic and open biceps tenodesis in the setting of rotator cuff repair between 2012 and 2016. Surgical, medical, and anesthetic complications, location, fellowship training, surgery year, and patient demographic data were recorded. Overall and specific complication rates were calculated and analyzed. Chi-square or Fisher exact tests were used to determine statistical significance. Results: Altogether, 1, 725 cases of arthroscopic biceps tenodesis and 1, 637 cases of open biceps tenodesis with arthroscopic rotator cuff repair were analyzed. No significant difference was found between overall complication rates between arthroscopic (11.4%) versus open (13.1%) biceps tenodesis ( P = 0.14). Although open tenodesis had statistically significant higher rates of wound healing issues (0.7% versus 0.2%, P = 0.02), hematoma/seroma formation (0.5% versus 0.1%, P = 0.02), nerve injury (1.5% versus 0.4%, P < 0.01), deep vein thrombosis (0.49% versus 0.12%, P ⩽ 0.05), and general anesthetic complications (0.75% versus 0.06%, P = 0.03), these rates remain comparably low. Shoulder arthroscopy fellowship-trained surgeons were more likely to use arthroscopic techniques than non–fellowship-trained surgeons ( P < 0.01) but had a higher complication rate ( P = 0.01). Discussion: No differences were found in overall complication rates between open and arthroscopic biceps tenodesis in the setting of rotator cuff repairs. Although open techniques had statistically significant higher rates of nerve injury, wound complications, and hematoma/seroma formation, this may not reflect clinical significance because these complication rates remained <2% in both techniques. Higher complication rates were seen among fellowship-trained surgeons, which may reflect greater case complexity. Both open and arthroscopic biceps tenodesis in the setting of rotator cuff repair show low complication rates, and the technique should be based on surgeon preference and patient factors. Level of Evidence: Level IV, case series